On the Validation of a Multiple-Network Poroelastic Model Using Arterial Spin Labeling MRI Data - Guo, Liwei; Li, Zeyan; Lyu, Jinhao; Mei, Yuqian; Vardakis, John C.; Chen, Duanduan; Han, Cong; Lou, Xin; Ventikos, Yiannis (Frontiers in Computational Neuroscience, 2019)
The Multiple-Network Poroelastic Theory (MPET) is a numerical model to characterise the transport of multiple fluid networks in the brain, which overcomes the problem of conducting separate analyses on individual fluid compartments and losing the interactions between tissue and fluids, in addition to the interaction between the different fluids themselves. In this paper, the blood perfusion results from MPET modelling are partially validated using cerebral blood flow (CBF) data obtained from arterial spin labelling (ASL) magnetic resonance imaging (MRI), which uses arterial blood water as an endogenous tracer to measure CBF. Two subjects – one healthy control and one patient with unilateral middle cerebral artery (MCA) stenosis are included in the validation test. The comparison shows several similarities between CBF data from ASL and blood perfusion results from MPET modelling, such as higher blood perfusion in the grey matter than in the white matter, higher perfusion in the periventricular region for both the healthy control and the patient, and asymmetric distribution of blood perfusion for the patient. Although the partial validation is mainly conducted in a qualitative way, it is one important step towards the full validation of the MPET model, which has the potential to be used as a testing bed for hypotheses and new theories in neuroscience research.